Activation of Endothelium by Borrelia burgdorferi In Vitro Enhances Transmigration of Specific Subsets of T Lymphocytes - Gergel, Edna I. (American Society for Microbiology, 2001)
Lyme disease, caused by Borrelia burgdorferi, is characterized by the accumulation of lymphocytes and monocytes in the affected tissue. Endothelial cells line the blood vessel walls and control the trafficking of inflammatory leukocytes from the blood into the surrounding tissues. A model of the blood vessel wall, consisting of human umbilical vein endothelial cells (HUVEC) grown on amniotic connective tissue, was utilized to examine the effects of B. burgdorferi on the transendothelial migration of T lymphocytes. Maximal migration occurred when the HUVEC-amnion cultures were preincubated with B. burgdorferi for 24 h and T lymphocytes were added for an additional 4 h, yielding a two- to fourfold increase compared to migration across unstimulated cultures. The number of T lymphocytes that migrated was proportional to the number added. The anti-inflammatory cytokine interleukin 10 (IL-10), added during activation of the HUVEC, significantly diminished (by an average of 70% ± 21%) the migration of T lymphocytes across endothelium stimulated for 8 or 24 h with B. burgdorferi, but not IL-1. Compared to the initially added population of T lymphocytes, the population that migrated across untreated endothelium or HUVEC activated with B. burgdorferi or IL-1 contained a significantly smaller percentage of CD45RA(+)RO(−) (naïve) cells and a greater proportion of CD45RA(+)RO(+) cells. The migratory population was also enriched for CD8(+) T lymphocytes when the endothelium was incubated with either control medium or B. burgdorferi, but not IL-1. B. burgdorferi thus activates endothelium in a manner that promotes the transmigration of T lymphocytes, and IL-10 inhibits this activation. These data further suggest that endothelium plays an active role in promoting the recruitment of specific subpopulations of T lymphocytes.